Global Supply Chain Trends in the Digital Economy Development and Its Individual Tools - Kolesnikov, A.V.; Zelinskaya, A.B; Bulantseva, L.V; Kosarev, V.E.; Breider, N.A (ExcelingTech, 2020)
Abstract The modern development of the world economy is accompanied by an increase in the role of science and innovation, the spread of information and communication technologies (ICT), including robotics. Today, ICT can be considered a leading factor in the arrangement of production and business processes, education, interaction of various subjects of society (state, organizations, and population), obtaining knowledge and information, leisure activities, and trade. ICT strengthen the material and technical base and stimulate socio-economic development, increasing the competitiveness and productive potential of the country’s economy. This topic is currently relevant, as the information society involves the widespread use of various information technologies in all areas of our activities. For example, at the moment in our society, a huge role is played by robotics, systems for distributing, storing and processing information that are based on computers. More and more inter-regional and international connections are being formed, which allows the exchange of information over long distances in the shortest possible time. In addition, the number of organizations using robotics is growing every day.